Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Given that f(x)=2x+1
a) find f(2)
b)find f^-1(x)
c)f^-1(7)


Sagot :

Answer:

a) [tex]f(2) = 5[/tex], b) [tex]f^{-1} (x) = \frac{x-1}{2}[/tex], c) [tex]f^{-1} (7) = 3[/tex]

Step-by-step explanation:

a) We evaluate the function at [tex]x = 2[/tex]:

[tex]f(2) = 2\cdot (2) + 1[/tex]

[tex]f(2) = 4+1[/tex]

[tex]f(2) = 5[/tex]

b) First, we determine the inverse of the function by algebraic means:

1) [tex]y = 2\cdot x + 1[/tex] Given

2) [tex]y +(-1) = 2\cdot x + [1+(-1)][/tex] Compatibility with addition/Associative property

3) [tex]y + (-1) =2\cdot x[/tex] Existence of additive inverse/Modulative property

4) [tex]2^{-1}\cdot [y+(-1)] = (2\cdot 2^{-1})\cdot x[/tex] Compatibility with multiplication/Commutative and associative properties

5) [tex][y+(-1)]\cdot 2^{-1} = x[/tex] Existence of multiplicative inverse/Modulative and commutative properties

6) [tex]x = [y+(-1)]\cdot 2^{-1}[/tex] Symmetry property of equality

7) [tex]x = \frac{y-1}{2}[/tex] Definitions of subtraction and division

8) [tex]f^{-1} (x) = \frac{x-1}{2}[/tex] [tex]x = f_{-1} (x)[/tex]/[tex]y = x[/tex]/Result

c)  Now we evaluate the expression obtained on b) at the given number:

[tex]f^{-1} (7) = \frac{7-1}{2}[/tex]

[tex]f^{-1} (7) = 3[/tex]